Indicadores de sustentabilidade em sistemas de rotação e sucessão de culturas com algodoeiro em plantio direto - MENEZES, Luiz Antonio Silva (2006)
The objective of this wok was to monitor sustainability indicators of soil involving the cotton plant in different crop rotation and succession systems, as well as to evaluate cover crop species which best adapt and that have longer longevity of decomposition as well as their effects on the physical and chemical properties and characteristics of soil. The field trials were developed in two sites. One experiment was conducted on the experimental Farm of Campus II of the UFG, in the town of Goiânia-GO and the other in the experimental area of the Fundação GO, in the town of Santa Helena de Goiás- GO. Both plant mass yield and decomposition longevity were evaluated in Goiânia by the litterbag process as well as also the physical and chemical characteristics of soil and cotton seed yield kg ha-1 and grain soybean kg ha-1, upon the effect of different cover crop species. The single covers which provided increased dry plant mass yields were grain sorghum followed by feather-grass, Crotalária + Millet and Brachiaria and in longevity, the decomposition of the plant mass was maximum in the first 22 days standing out the mixture Mucuna + grain sorghum which showed highest residual plant mass yield. Most of the treatments involving the cover plant species in Goiânia presented the values of resistance to penetration (RP) within the ranges considered from high to low. Crotalária (Crotalária juncea) presented in Goiânia the lowest RP in solo, this being able to be the best option for the farming system management. The lowest values of RP found at Santa Helena were obtained by the cover crops Pigeon pea, Millet and grain sorghum. The crop rotation systems studied did no differ as to the effect of soil density, total porosity, macroporosity, microporosity and average diameter of aggregates. The elements P and Ca proved limiting as well as pH, V% and CEC for the cotton crop. There was no influence of the cover crop species on yield of the cotton plant and soybean.